2021
DOI: 10.3390/children8110965
|View full text |Cite
|
Sign up to set email alerts
|

Opsoclonus-Myoclonus Syndrome in Children and Adolescents: A Therapeutic Challenge

Abstract: Opsoclonus-myoclonus syndrome (OMS) is a neurological non-fatal disease that usually responds to immunotherapies. However, the real challenge is to counteract the high frequency of relapses and long-term developmental sequelae. Since the OMS is extremely rare, a common consensus regarding therapeutic guidelines is still lacking. The goals of this study were to test whether ACTH was superior to other immunotherapies and to investigate whether an early treatment could improve the outcome. Sixteen children affect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…However, early treatment is indicated and has been shown to be associated with better long-term outcomes [ 53 ]. Mizia-Malarz et al found that long-term sequelae occurred in all patients that were treated late, but only in 42% of patients that were treated early [ 54 ]. In some cases whereby OMAS is associated with neuroblastoma, tumor resection has led to the alleviation of symptoms, but, in others, the symptoms persisted [ 30 , 37 , 55 ].…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…However, early treatment is indicated and has been shown to be associated with better long-term outcomes [ 53 ]. Mizia-Malarz et al found that long-term sequelae occurred in all patients that were treated late, but only in 42% of patients that were treated early [ 54 ]. In some cases whereby OMAS is associated with neuroblastoma, tumor resection has led to the alleviation of symptoms, but, in others, the symptoms persisted [ 30 , 37 , 55 ].…”
Section: Reviewmentioning
confidence: 99%
“…In some cases whereby OMAS is associated with neuroblastoma, tumor resection has led to the alleviation of symptoms, but, in others, the symptoms persisted [ 30 , 37 , 55 ]. Adrenocorticotropic hormone (ACTH) [ 54 ], steroid therapies [ 56 , 57 ], and IVIG are commonly used in the treatment of OMAS. A randomized controlled trial of 53 participants demonstrated a significantly superior response in patients who were given a combination of IVIG and prednisolone as compared to prednisolone alone [ 58 ].…”
Section: Reviewmentioning
confidence: 99%
“…[19] An early diagnosis and treatment correlate with an improved prognosis and a decreased likelihood of neurological or neuropsychiatric complications. [20] Long-term outcomes following OMS in children have shown that patients typically achieve relatively good recovery, albeit incompletely in terms of motor function. [21,22] However, cognitive, and behavioral deficits are often observed, which can significantly impact functioning.…”
Section: Introductionmentioning
confidence: 99%